Caudillos, comrades, and relatives - Pereyra Chávez, Nelson E. (2020)
This paper reconstructs the history of the Peruvian Communist Party-Red Flag in the city of Ayacucho, from the individual memories of its militants. Individual memories that come together in a sole emblematic memory of the party. Through these memories, this paper penetrates the history of the group and identifies its main characteristic. Thus, in Ayacucho, Red Flag was a group of friends, relatives and neighbors gathered around an ideology but, above all, around a caudillo or charismatic leader who acted as the father of a family with political children. This group had an ephemeral peasant and neighborhood base, which disappeared when the party took an ideological turn at the end of the 1970s, without being able to become an adequate channel of intermediation with the Peruvian State.